Il testo poetico della giustizia. Alberico e Scipione Gentili leggono la Repubblica di Platone - Iurlaro, Francesca (ΠΗΓΗ/FONS, 2017)
The present contribution will shed light on the reception of Plato’s Republic (as well as of Aristotle’s Poetics) within the context of the early modern debate concerning poetry and poetic theory. Among the protagonists of this vivid debate, the two brothers and jurists Alberico (1552-1608) and Scipio Gentili (1563-1616) played a significant role in vindicating the existence of a strong relationship between law and poetry. In order to address this question, it has first to be assessed to which auctoritates of the past they relied upon to justify this relationship (and how they conceive of it); secondly, this article will read this phenomenon within the context of the 16th century debate concerning poetic theory. In this respect, Plato’s Republic plays a fundamental role in clarifying the conceptual stakes of such debate. In this perspective, I will argue that the relationship between law and poetry is addressed by both the Gentili brothers in terms of an analogy between poetry and rhetoric, and between rhetoric and law (in an anti-Platonic vein); on the other hand, the Gentilis seem to support Plato’s rejection of Homeric poetry in order to assess the primacy of another poet: Virgil. To conclude with, I will suggest that the parallel between poetry and justice (drawn by Plato in his Republic) might provide a possible interpretation of the relationship between law and poetry in the thoughts of Alberico and Scipio Gentili, where an implicit platonic criterion of justice seems to validate the legitimacy of the poetic exemplum.